THE CORRELATION BETWEEN INTEREST IN LISTENING TO ENGLISH SONGS AND VOCABULARY MASTERY OF THE SECOND SEMESTER STUDENTS OF ENGLISH STUDY PROGRAM FKIP UNIVERSITAS RIAU - Ria Syafitri; Supriusman Supriusman; M. Syarfi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research aims to find out if there is a significant correlation between the interest in listening to English songs and vocabulary mastery of the second semester students of English Study Program FKIP Universitas Riau. The sample of this research consisted of 36 students which was taken by using Cluster Random Sampling Technique. The data were collected through questionnaire in order to measure students’ interest in listening to English songs and AVK test to measure students’ vocabulary mastery. The results showed that the students have high interest in listening to English songs and have average ability in mastering vocabulary through Aural Vocabulary Knowledge (AVK). Further, the significant correlation was discovered between both variables with a moderately positive correlation.Key Words: Interest, Listening, English Songs, Vocabulary Mastery